Analisis Sanksi Terhadap Nasabah Mampu Yang Menunda-Nunda Pembayaran Dalam Perspektif Ekonomi Syariah : (Studi Fatwa DSN-MUI No. 17/DSN-MUI/IX/2000) - Mawaddah Mawaddah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the implementation of sanctions against wealthy customers who delay payments in the perspective of DSN-MUI Fatwa No. 17/DSN-MUI/IX/2000. The study was conducted at PT. BPRS Alwashliyah Gunung Krakatau Medan with a normative and empirical legal approach. The results of the study indicate that the application of sanctions against customers who delay payments is an effort by banks to maintain the smoothness of the financing system. The application of the DSN-MUI fatwa provides a legal basis for Islamic banks in imposing sanctions on wealthy customers who neglect to fulfill their obligations. This fatwa also strengthens the position of banks in the Indonesian civil law system.